Sunnah, Scientific Method and the Law: Foundations for an Islamic Response to Technological Civilization - Lubna Ameen Khan; Dr. Muhammad Asim Shahbaz; Fouzia Ayub (Journal of Religion and Society, 2025)
This study explores the epistemological and ethical foundations of an Islamic response to modern technological civilization by examining the interrelationship between Sunnah, the scientific method, and the law (Sharīʿah). The research argues that the Sunnah embodies a dynamic model of inquiry rooted in observation, verification, and moral responsibilityprinciples that resonate with the scientific method yet transcend it by integrating divine guidance and ethical purpose. Through a comparative analysis of Islamic jurisprudence and modern philosophy of science, the study demonstrates that Islamic epistemology provides a holistic framework wherein knowledge (ʿilm) is inseparable from moral accountability (taklīf). Furthermore, it emphasizes that technological advancement, when divorced from spiritual and ethical parameters, leads to moral disorientation and social imbalance. The paper proposes a revival of ijtihād in scientific ethics, encouraging Muslim scholars and technologists to formulate policies grounded in the Qur’ānic vision of maṣlaḥah (public good) and ʿadl (justice). By reconnecting the scientific spirit with prophetic wisdom, the research establishes a foundation for an integrated, ethical, and purposeful technological future under the guidance of Islamic law. Keywords: Scientific Method, Islamic Epistemology, Technological Civilization, Ijtihād, Ethical Framework, Islamic Philosophy of Science